Vaccines for tumor prevention: a pipe dream? - Guido Forni (Journal of Infection in Developing Countries)
Whether or not a tumor expresses peculiar antigens that differentiate it from normal cells was intensively investigated in the 1950s. A conclusive answer was provided in 1960 when George Klein showed that a tumor can be rejected by the immune response elicited by a vaccine administered to the same mouse in which the tumor was induced. Whether immunogenicity was a feature restricted only to tumors artificially induced by viruses or by high doses of chemical carcinogens was then hotly debated until Terry Boon showed, in the 1980s, that almost any tumor can be recognized by a syngeneic immune system triggered by an appropriate cancer vaccine. However, the therapeutic efficacy of vaccine-induced immunity against an advanced tumor is marginal. The combination of an anti-tumor vaccine with new sophisticated maneuvers to contrast tumor-induced suppression may yield new and effective therapeutic strategies. Also, the exploitation of tumor vaccines to prevent tumors in cohorts of people with a specific risk of cancer may become a fresh strategy with great potential to control tumor onset.